Analisis Yuridis Praktik Diskriminasi dalam Penjualan Kargo Angkutan Udara (Studi Kasus Putusan KPPU Nomor 7/KPPU-I/2020) - Tariq Hidayat Pangestu (Komisi Pengawas Persaingan Usaha, 2021)
AbstractOne form of activity that is prohibited in business competition law is the practice of discrimination which is a form of market domination. One of the cases of discriminatory practices is related to air cargo transportation services involving Lion Air Group in KPPU Decision Number 07/KPPU-I/2020. Based on the evidence of the elements of Article 19d of Antitrust Law and the impact caused by this discriminatory practice, KPPU imposes sanctions on the reported parties to stop discriminatory practices and fines but do not need to be implemented. By using doctrinal/normative juridical research, it can be concluded that the fulfillment of the elements of article 19d of Antitrust Law is included in the determination of the relevant market and the resulting impact is in accordance with the rules stipulated in KPPU Regulation Number 3 of 2011 and the construction of the rule of reason. In addition, the suspension of sanctions has been in accordance with and obtain legitimacy to be handed down with several considerations that should be included but are not contained in this decision.Keywords: Discrimination; Relevant Market; Decision; Lion Air Group; Rules of Reason.